Vegetables - Importance of Quality Vegetables to Human Health 2018
DOI: 10.5772/intechopen.74472
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Fruits and Vegetables: Review from Sub-Saharan Africa

Abstract: A fruit is defined as the edible part of a plant that consists of the seeds and surrounding tissues, while vegetables are plants cultivated for their edible parts. Fruits and vegetables are important sources of micronutrients and dietary fibres and are components of a healthy diet, which help in preventing major diseases. Due to the fact that fruits and vegetables have health promoting properties, they contribute to dietary guidance. This chapter defines the basic concepts related to health benefits of fruits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…Some common fruits like citrus (e.g., lime, lemon, orange, tangerine, grape), guava, cashew, mango, pawpaw, pineapple, avocado, banana, African star apple, sweetsop/ sugar apple, breadfruit, soursop, African bush mango, passion fruit, apple, dates ( 58 ) and vegetables (e.g., tomatoes, okra, eggplant, cucumber, beets, garlic, onion, and ginger) found in sub-Saharan Africa may be of nutritional psychiatry relevance ( 58 ). These fruits and vegetables have high levels of micronutrients such as zinc, magnesium, selenium, iron, and vitamins ( 59 , 60 ).…”
Section: Foods and Food Compounds That Affect Psychiatric Biomarkersmentioning
confidence: 99%
“…Some common fruits like citrus (e.g., lime, lemon, orange, tangerine, grape), guava, cashew, mango, pawpaw, pineapple, avocado, banana, African star apple, sweetsop/ sugar apple, breadfruit, soursop, African bush mango, passion fruit, apple, dates ( 58 ) and vegetables (e.g., tomatoes, okra, eggplant, cucumber, beets, garlic, onion, and ginger) found in sub-Saharan Africa may be of nutritional psychiatry relevance ( 58 ). These fruits and vegetables have high levels of micronutrients such as zinc, magnesium, selenium, iron, and vitamins ( 59 , 60 ).…”
Section: Foods and Food Compounds That Affect Psychiatric Biomarkersmentioning
confidence: 99%
“…One study indicated that fruits and vegetable intake is low among adolescents and correlates with low consumption (Labyak, Jahan-Mihan, Seabrooks-Blackmore & Rodriguez, 2017). Several studies highlight positive benefits of fruit and vegetable consumption including improvement in brain and memory function and overall wellbeing (Liu, 2003;Slavin & Lloyd, 2012;Amao, 2018). One study concluded that the rate and frequency of fruits and vegetable consumption among participants increase in tandem with the health education and promotional benefits received (Nti, Hagan, Bagina, & Seglah, 2011).…”
Section: Meal Outsourcing Servicesmentioning
confidence: 99%
“…Fruits are essential in the human diet and their consumption has been correlated with multiple health benefits as they are dense in vitamins, minerals, fibre and many bioactive compounds (Amao, 2018). Their medicinal properties have been linked to their potent antioxidant activities which reduce the risks of short life span, cardiovascular diseases, stroke, obesity, diabetes, neuronal dysfunction and cancer (Boffetta et al., 2010; Oyebode et al., 2014; Rolls et al., 2004).…”
Section: Introductionmentioning
confidence: 99%